Best Practices of Learning, Teaching and Assessment in Virtual Classrooms - CRAȘOVAN, Mariana (Presa Universitară Clujeană, 2023)
The Covid-19 pandemic, which has engulfed the entire world, caught all educational systems off guard. They looked for solutions to continue education, even as most educational institutions were closed. What brought as a positive element, if we can say so, the COVID-19 pandemic was the rapid adaptation of educational systems to an unprecedented situation in recent human history. The teaching staff had to participate in training courses, either learn alone (self-directed) or learn together with colleagues, in order to be able to continue the education beyond the confines of direct in-person meetings within school premises. The utilization of diverse communication methods, ranging from social networks to virtual meetings facilitated by the Internet and computers, as well as hybrid approaches, constituted the solutions devised at that time — some proving more efficacious than others.